Corrosion control of Buried Low Carbon Steel Structure by Using Alteration Medias method - Merzah, Amel S.; Hafiz, Mohammed H.; Mohammed, Sarah k. (Al-Khwarizmi Engineering Journal, 2017)
Abstract The aim of the present work is to control of metal buried corrosion by alteration the media method. This method depended on the characteristics of each media. The corrosion rates in different media (soil, sand, porcelanite stone and gravel) for specimens of low carbon steel were measured by two methods weight loss method and polarization method, weight loss measured by buried specimens in these medias separately for 90 days. The polarization method includes preparing of specimen and salt solutions have electrical resistivity equivalent electrical resistivity of these media. The corrosion rate of two method results in (soil > sand> porcelainte stone> gravel). The lower corrosion rate happened in gravel media because of characteristics of high electrical resistivity and lower porosity for gravel while the higher corrosion rate occurred in the soil. Keywords: Low carbon steel, corrosion rate, medias, electrical resistivity, soil, sand, porcelanite media, gravel.